I come from a beautiful place - Mansour, Carol (Lebanon, 2010)
Five protagonists from different countries whose life and experience as refugees in Lebanon is intertwined. Through their stories, the film gives a raw portrait of loss, fear, persecution and at the same time hope.
Verzio Film Festival Submission
Keywords: Documentary films